2006
DOI: 10.3390/medicina43030024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the prolonged thoracic epidural analgesia on ventilation function and complication rate after the lung cancer surgery

Abstract: Thoracic epidural analgesia has been considered to have a good anesthetic efficacy and to decrease the postoperative complication rate, while its effect upon the ventilation function is still the topic of many clinical studies. The aim of this study was to evaluate the course of early postoperative period using thoracic epidural analgesia. Material and methods. A total of 453 patients undergoing the operation due to the non–small cell carcinoma were selected and examined. Their postoperative complications and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…However, patients who received this management also experience a variety of complications after LCS, such as ICN. [13][14][15][16][17][18][19][20] Non-invasive therapy, such as UGPRF has been reported to relieve various pain disorders. However, very few evidence regarding this issue is available.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, patients who received this management also experience a variety of complications after LCS, such as ICN. [13][14][15][16][17][18][19][20] Non-invasive therapy, such as UGPRF has been reported to relieve various pain disorders. However, very few evidence regarding this issue is available.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection remains the mainstay of effective treatment for such patients. However, patients who received this management also experience a variety of complications after LCS, such as ICN [13–20] …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kopeika et al [15] showed TEA provided superior postoperative pain control than intramuscular opioid administration after pulmonary resection, and found a tendency of less frequent postoperative atrial fibrillation among those who received TEA. Oka et al [17] compared TEA with bupivacaine and TEA with morphine for postoperative analgesia for pulmonary resection and found that occurrence of atrial fibrillation and supraventricular tachycardia within 3 days after surgery was less for TEA with bupivacaine.…”
Section: Discussionmentioning
confidence: 99%